Angiotensin peptides in spontaneously hypertensive and normotensive Donryu rats - Campbell, D J; Duncan, A M; Kladis, A; Harrap, S B (Hypertension (Dallas, Tex. 1979), 1995)
The renin-angiotensin system has been implicated in the pathogenesis of hypertension in spontaneously hypertensive rats (SHR). Given that SHR may have normal or suppressed plasma levels of renin and angiotensin peptides, we examined whether the tissue levels of angiotensin peptides are elevated in these rats. We measured angiotensin-(1-7) [Ang-(1-7)], Ang II, and Ang I in plasma, kidney, adrenal, heart, aorta, brown adipose tissue, lung, and brain of male SHR and normotensive Donryu rats at 6, 10, and 20 weeks of age. SHR had higher blood pressures and ratios of heart weight to body weight at all ages. Plasma renin levels of SHR were 13% to 32% of the levels of Donryu rats. Although plasma angiotensin-converting enzyme activity was lower in SHR than in Donryu rats, lung was the only SHR tissue with a reduced Ang II-Ang I ratio. Ang II levels in SHR adrenal were 24% to 42% of the levels of Donryu adrenal, and for SHR plasma, aorta, brown adipose tissue, and lung, Ang II levels were 38% to 93% of the levels of Donryu rats. For kidney and heart, Ang II levels were similar in SHR and Donryu rats at 6 weeks of age although suppressed in SHR at 10 and 20 weeks. Moreover, brain Ang II levels were higher in SHR than Donryu rats at 6 weeks of age and similar at 10 and 20 weeks of age.